D-109 Defining a potent new class of latency reversing agents devoid of toxicity and detrimental cell activation that enhance CTL/NK cell killing. (April 2018) - Gramatica, Andrea; Schwarzer, Roland; Montano, Mauricio; Herzig, Eytan; Packard, Thomas; Greene, Warner C.
Abstract : Despite long-term administration of antiretroviral therapy (ART), HIV-1 persists in a broadly distributed latent reservoir mainly comprised of resting CD4+ T cells. Cells harboring latent provirus typically display little to no HIV-1 gene expression and thus remain invisible to the immune system. To achieve a durable sustained viral remission in HIV-infected patients off ART (a functional cure), it will be important to both "reduce the size of the reservoir and to control viral rebound by eliciting an effective immune response capable of restraining viral spread from the smaller reservoir. This approach will likely require the combined use of potent and safe latency-reversing agent (LRA) and a therapeutic HIV vaccine. Our recent studies have shown that activators of the AKT/mTOR pathway form a promising group of LRAs. Our interest has focused on two small molecules, SB-216763 and Tideglusib that commonly inhibit glycogen synthase kinase-3 (GSK-3). This inhibition triggers a metabolic shift to glycolysis and results in sequential activation of mTORC2, AKT, and mTORC1. Both compounds are known to have high tissue penetration including the brain. We found that these GSK-3 inhibitors potently activate latent HIV-1 in both a tissue-based model of HIV latency formed in primary CD4 T cells, and in CD4 T cells isolated from HIV-infected patients. In some experiments, these agents are more potent than anti-CD3/anti-CD28 antibodies even though the GSK-3 inhibitors do not appear to induce T cell activation (measured by changes in CD69 and CD25 expression). Finally, in contrast to the undesirable compromise of CTL/NK function associated with many first generation LRAs (PKC activators, HDAC inhibitors), the GSK-3 inhibitors actually enhance CTL and NK cell effector function. In summary, our findings reveal GSK-3 inhibitors as an interesting new class of potent, safe, non-cell activating LRAs. Next, it will be key to define their activity in vivo using SIV-infected macaques on suppressive ART. The fact that tideglusib is already in phase II human trials for myotonic dystrophy and autism could accelerate its ultimate testing as an LRA in HIV-infected patients.